2014
DOI: 10.1007/s00268-014-2589-9
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial: Nasoenteric Tube or Jejunostomy as a Route for Nutrition After Major Upper Gastrointestinal Operations

Abstract: The two enteral routes were associated with the same number of complications. However, the presence of a jejunostomy allowed enteral therapy for longer periods, especially in patients with complications, thus avoiding the need for parenteral nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…A randomized clinical study that compared nasoenteric tubes to jejunostomy feeding in upper gastrointestinal tract cancer patients showed that the length of enteral feeding use was less in the nasoenteric group and parenteral feeding was required more frequently than in jejunostomy feeding group. Complications related to the different feeding routes were similar between the two groups [94]. A recent review investigated the best route for enteral nutrition following esophagectomy (oral intake, jejunostomy, or nasojejunal tube feeding) in terms of postoperative complication rates, percentage of patients meeting their nutritional needs, weight loss, tube feeding complications, mortality, patient satisfaction, and length of hospital stay.…”
Section: Type Of Feedingmentioning
confidence: 97%
“…A randomized clinical study that compared nasoenteric tubes to jejunostomy feeding in upper gastrointestinal tract cancer patients showed that the length of enteral feeding use was less in the nasoenteric group and parenteral feeding was required more frequently than in jejunostomy feeding group. Complications related to the different feeding routes were similar between the two groups [94]. A recent review investigated the best route for enteral nutrition following esophagectomy (oral intake, jejunostomy, or nasojejunal tube feeding) in terms of postoperative complication rates, percentage of patients meeting their nutritional needs, weight loss, tube feeding complications, mortality, patient satisfaction, and length of hospital stay.…”
Section: Type Of Feedingmentioning
confidence: 97%
“…3 Both routes were associated with a similar number of complications and a similar LOS. Nevertheless, the JT route allowed EN for longer periods.…”
Section: Discussionmentioning
confidence: 95%
“…Table 3 summarises studies on EN after oesophagectomy. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Although the use of EN is not without its disadvantages, the benefits outweigh the risks. Early EN was compared with delayed nutrition by Wang et al, and was found to be associated with a short LOS, fewer incidences of pneumonia and better nutrition outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] pointed out that a jejunostomy allows enteral therapy for longer periods, especially in patients with complications. In our cases 3 and 4, progressive increase of caloric intake could be smoothly performed through the feeding jejunostomy tube from the day after onset of anastomotic failure.…”
Section: Discussionmentioning
confidence: 99%